The Dynamic Nature of Self‐Assessed Health (SAH) as a Function of Negative and Positive Affects among Cardiac Patients. Issue 3 (24th November 2017) - Peleg, Shira; Drori, Erga; Banai, Shmuel; Finkelstein, Ariel; Shiloh, Shoshana
Abstract : Background: Self‐assessed health (SAH) predicts health outcomes above and beyond medical variables. One of the explanations for this robust finding is the sensitivity of SAH to changes in multiple aspects of health, including emotional factors. We assessed the dynamic nature of SAH by longitudinally examining the associations between initial and change levels of SAH and positive affect (PA) and negative affect (NA). Methods: Participants were 138 cardiac patients undergoing coronary angioplasty. Self‐report questionnaires measured SAH, PA, and NA, one day and one month after catheterisation. Results: Means of SAH and NA did not change between measurement points, but PA decreased. Cross‐lagged analysis indicated that the best model for representing the data included a path from affect at hospitalisation to SAH one month later; that is, lower NA (but not PA) at hospitalisation predicted higher SAH a month later. A latent change model analysis also revealed that NA (but not PA) at hospitalisation predicted changes in SAH (but SAH did not predict changes in negative or positive affect); and that increases in positive affect and decreases in negative affect were linked to increases in SAH. Conclusions: These findings highlight the importance of NA as an indicator of SAH and SAH change, and provide further insights into the dynamics of SAH in cardiac patients.